Electrophysiological Properties of Adult Zebrafish Oligodendrocyte Progenitor Cells - Tsata, Vasiliki; Kroehne, Volker; Reinhardt, Susanne; El-Armouche, Ali; Brand, Michael; Wagner, Michael; Reimer, Michell M. (Frontiers in Cellular Neuroscience, 2019)
Low remyelination efficiency after spinal cord injury is a major restraint to successful axonal and functional regeneration in mammals. In contrast, adult zebrafish can (i) regenerate oligodendrocytes and myelin sheaths within 2 weeks post lesion, (ii) re-grow axonal projections across the lesion site and (iii) recover full locomotor function within 6 weeks after complete spinal cord transection. However, little is known about the intrinsic properties of oligodendrocyte progenitor cells (OPCs), the remyelinating cells of the central nervous system. Here, we demonstrate that purified OPCs from the adult zebrafish spinal cord are electrically active. They functionally express voltage-gated K+ and Na+ channels, glutamate receptors and exhibit depolarizing, tetrodotoxin-sensitive spikes, as previously seen in rodent and human OPCs. Furthermore, we show that the percentage of zebrafish OPCs exhibiting depolarizing spikes and Nav-mediated currents is lower as compared to rodent white matter OPCs, where these membrane characteristics have been shown to underlie OPC injury susceptibility. These findings imply that adult zebrafish OPCs resemble electrical properties found in mammals and represent a relevant cell type towards understanding the biology of the primary cells targeted in remyelination therapies for non-regenerative species. The in vitro platform introduced in this study could be used in the future to (i) elucidate how membrane characteristics of zebrafish OPCs change upon injury and (ii) identify potential signaling components underlying OPC injury recognition.